2020
DOI: 10.1007/s42729-020-00222-0
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Cultivation Approach to Increase the Culturable Bacterial Diversity in the Rhizobiome of Plants

Abstract: The use of high-throughput DNA sequencing (HTS) has revealed the great diversity of rhizobacteria in plant rhizospheres; however, only a minor portion (≤ 1%) of rhizobacteria belonging to few taxa can be cultured under laboratory conditions. In recent years, in situ cultivation has opened a window to explore a greater diversity of bacterial taxa in the environment. Here, we explored the total and culturable rhizobacterial communities associated with the rhizosphere of wheat plants by using 16S rRNAbased HTS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
(68 reference statements)
1
17
0
Order By: Relevance
“…Acuña et al (2020) found that in the rhizobiome of wheat, Proteobacteria and Acidobacteria were the most dominant phyla (Smit et al 2001). Proteobacteria responded quickly to unstable carbon and phosphorus nutrients and showed the ability to grow rapidly and adapt to diverse plant rhizosphere environments (Acuña et al 2020). In this study, we observed that Proteobacteria occupied higher abundance in all the bacteria during the whole wheat growth period and has little change.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Acuña et al (2020) found that in the rhizobiome of wheat, Proteobacteria and Acidobacteria were the most dominant phyla (Smit et al 2001). Proteobacteria responded quickly to unstable carbon and phosphorus nutrients and showed the ability to grow rapidly and adapt to diverse plant rhizosphere environments (Acuña et al 2020). In this study, we observed that Proteobacteria occupied higher abundance in all the bacteria during the whole wheat growth period and has little change.…”
Section: Discussionsupporting
confidence: 46%
“…The phylum Proteobacteria, which is metabolically versatile and genetically diverse, comprises the largest fraction of the bacterial community in soil ecosystems and is more dominant than the phylum Acidobacteria (Smit et al 2001;Wu et al 2013). Acuña et al (2020) found that in the rhizobiome of wheat, Proteobacteria and Acidobacteria were the most dominant phyla (Smit et al 2001). Proteobacteria responded quickly to unstable carbon and phosphorus nutrients and showed the ability to grow rapidly and adapt to diverse plant rhizosphere environments (Acuña et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…in association with the lichen Usnea sp., Haplopappus sp., and Gaultheria sp. The low bacterial number can be partly explained due to the antimicrobial activities of some of these wild plants and the lichen [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], and the low recovery rates of culturable bacteria from the rhizosphere and phyllosphere of plants [ 83 , 84 ] under the conditions used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…After standardization, fingerprint analyses were performed using genomic DNA from other two culture collection Azospirillum sp. CRISPR-harboring strains, as well as nine other native Azospirillum spp., and 38 native strains of different taxa previously isolated from wheat rhizosphere and root endosphere from the Region de La Araucanía [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…strain B506 (WGS: BADK01000001:BADK01001143) [ 8 ], both harboring CRISPR loci, were also acquired from JCM-RIKEN and used as control strains for PCR specificity assays. Additional control strains consisted of Azospirillum strains isolated from the wheat rhizosphere in Chile [ 10 ], and strains from the genera Bacillus , Microbacterium , Chitinophaga , Arthrobacter , Georgenia , Psychrobacillus , Roseomonas , Bosea and Leifsonia previously isolated from the wheat rhizosphere (20 strains), and endosphere (18 strains) [ 11 ]. All bacteria used in this study are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%